Pengembangan Buku Interaktif 3D Audio Visual pada Materi Tutorial Pengembangan Media Pembelajaran Berbasis Studi Kasus Adaptif untuk Peningkatan Kompetensi Keterampilan Mahasiswa PPG Seni Budaya - Iriaji; Titi Rahayuningsih; Yuliati; Risa Septyana; Eka Putri Surya; Alby Aruna; Adinda Marcelliantika (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study aims to develop a 3D audio-visual interactive book on tutorial materials for developing adaptive case-based learning media to enhance the skill competencies of PPG Art and Culture students. The methodology includes needs analysis, interactive book design, and effectiveness evaluation. This interactive book is designed to provide an immersive and comprehensive learning experience through the use of 3D and audio-visual technology. The results indicate that this interactive book significantly improves students' understanding and skills in developing adaptive, case-based learning media. Evaluations through surveys and in-depth interviews confirm that the book is effective in supporting a more innovative and interactive learning process. This study makes a significant contribution to the development of modern and relevant learning materials in contemporary education.